Positive Media Fostering Children And Adolescents Well Being - Dr. Nidhi Chadha, Goswami Ganesh Dutta (International Journal of Advanced Science and Technology, 2020)
The ensuing paper addresses an emerging trend witnessed in the present day movies and cinema i.e. can positive media psychology can encourage happiness enhancing behaviours? It is quite a known fact that media was traditionally considered as mere entertainment; psychologically speaking an emphasis was laid just on the hedonic aspect but today, a paradigm shift is seen with the upcoming movies which comprises of eudaimonic motivation.  Parents would not like their children to see television and movies often as they would not study or learn inappropriate behaviour. To attend this question, the researcher’s replies with an overview of Indian Hindi movies that focus on positivity, life goals and motivation and also it can be asserted that it continues to have a great impact on the psyche of children and adolescents thus may serve as a promising area of study in human psychology. Therefore, this qualitative research aims to explore popular Hindi movies that thematically explore that media can induce emotions that contribute to well-being.